2008
DOI: 10.1021/jo801356y
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene glycol) Grafted onto Dowex Resin: An Efficient, Recyclable, and Mild Polymer-Supported Phase Transfer Catalyst for the Regioselective Azidolysis of Epoxides in Water

Abstract: In this study, an efficient method was designed to graft poly(ethylene glycol) effectively onto commercial Dowex resin. The catalytic efficiency of the copolymer obtained as a new solid-liquid phase transfer catalyst was studied. It was proved that this organocatalyst is an efficient heterogeneous catalyst for regioselective azidolysis of epoxide in water and gave azidohydrin in excellent yield under mild reaction conditions. The polymeric catalyst was easily recovered by simple filtration and showed no apprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…Hence, from industrial point of view, polymer-anchored catalyst is more desirable in order to simplify catalyst separation from the reaction mixture and its reuse thereby the need for complex chromatographic techniques can be avoided for product separation and isolation [3][4][5][6][7][8]. To circumvent the problem of separation of catalyst from the reaction mixture, for the first time Regen [9] reported anchoring the phase transfer catalysts to a polymer backbone and suggested the name ''Triphase Catalysis''.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, from industrial point of view, polymer-anchored catalyst is more desirable in order to simplify catalyst separation from the reaction mixture and its reuse thereby the need for complex chromatographic techniques can be avoided for product separation and isolation [3][4][5][6][7][8]. To circumvent the problem of separation of catalyst from the reaction mixture, for the first time Regen [9] reported anchoring the phase transfer catalysts to a polymer backbone and suggested the name ''Triphase Catalysis''.…”
Section: Introductionmentioning
confidence: 99%
“…Excellent yields of the desired β-azido alcohols are obtained with a reversal of regioselectivity indicating attack at the less substituted carbon of the aliphatic oxiranes (Entries 2-7, Table 2), while styrene oxide (Entry 1, Table 2), as an aryl oxirane formed the major product as 2-azido-2-phenylethanol, by the attack of azide nucleophile at the benzylic position, this is due to the formation of a stable benzyl carbocation during mechanism, is evidenced by electronic factors [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40], whereas in the case of aliphatic oxiranes (Entries 2-7, Table 2), steric factors predominate over electronic factors, thereby facilitating attack at the less hindered carbon atom of the oxirane ring. Furthermore, oxiranes derived from cycloalkenes, such as 7-oxabicyclo [4.1.0]heptanes (Entry 2, Table 2), reacted smoothly in SN2 fashion to afford the corresponding azidohydrine; and the reaction was completely anti-sterioselective, thus resulting in trans isomer only.…”
Section: Resultsmentioning
confidence: 99%
“…Some heterogeneous catalysts, relying on the use of traditional solid acids such as amberlite IRA-400 supported azide [33]. Dowex resin grafted by poly ethylene glycol [34], oxone [35], sodium azide supported on Zeolite CaY [36], ammonium salt of a hetero poly acids [37], quaternized ammonium salt [38] and quaternized amino functionalized cross linked polyacrylamide [39] have been reported. Recently, hot water promoted azidolysis also reported [40].…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind and as a part of our research to develop green chemistry by using water as reaction medium, [21][22][23][24][25] we report herein our results on regioselective ring opening of various epoxides with azide ion using a,a¢,a¢¢-N-hexakis(triethyl-ammoniummethylene chloride)-melamine as an efficient multi-site phasetransfer catalyst, in water (Scheme I). They found that this MPTC catalyst has higher activity than the commercially available single-site phase transfer catalyst in the alkylation of phenylacetonitrile with 1-bromobutane.…”
Section: Resultsmentioning
confidence: 99%